Seroprevalensi dan Faktor Risiko Rabies pada Anjing di Daerah Endemis Kabupaten Sukabumi - Ardilasunu Wicaksono; Abdul Zahid; Etih Sudarnika; Dordia Anindita Rotinsulu; Denny Widaya Lukman; Sri Murtini; Yusuf Ridwan (Institut Pertanian Bogor, 2021)
Sukabumi District is reported to date as an endemic rabies area in West Java Province. In supporting the rabies control programs, the occurrence of rabies needs to be determined to decrease the number of cases. This research aims to determine the seroprevalence of rabies and identify the risk factors associated with rabies in the district. The research was conducted in Jampang Tengah and Cisolok sub-districts with positive rabies cases on dogs and humans. The blood samples were taken from 191 selected dogs using simple random sampling. Rabies antibody titer was measured using ELISA, and the risk factor was identified using selected dogs’ data classified into intrinsic and extrinsic characteristics. Data were analyzed using the chi-square test and the calculation of the odds ratio. The results showed that the seroprevalence of rabies was 7.9% (4.9-10.9%). The average antibody titer was 0.23 EU with a minimum value of 0.03 EU and a maximum of 0.96 EU. Thus, as high as 7.8% of the population showed rabies seropositivity from the unvaccinated dogs, while among the vaccinated dogs, only 8.0% of the population with rabies protective antibody titer. The significant risk factor of rabies seroprevalence is the typology of raising area (p = 0.003), revealing that the dogs raised in the coastal area had the odds of 5.8 (1.6-21.2) higher to get the rabies seropositivity than the dogs raised in the highland area. Keywords: antibody titre, dogs, rabies, risk factor, seroprevalence